Urban Interiority in the Anthropocene - Arrizabalaga, Nerea Feliz (UI Scholars Hub, 2020)
This paper explores how interior design could amplify the current discourse on sustainability within urban public space. The consideration of a number of contemporary authors that are questioning the traditional notion of interiority situates this paper within an expansive understanding of interiority in the context of the Anthropocene. Interiority is considered as a transferable condition based on modes of interior occupation, that can take place on the outdoors, and is often found in public spaces within dense urban areas. In the face of an upcoming biodiversity crisis, this text advocates for a necessary disciplinary shift away from traditional anthropocentric views, towards a multispecies conception of the built environment. Both the ideas and the case studies in this article seek to expand the role of interior elements, both semiotics and performance, to foster inclusivity of non-human species, in particular insects, in city environments. Two design proposals illustrate how interior design tactics might positively contribute to raising awareness about this underacknowledged population, and at the same time, help cultivate a sense of intimacy between us and the multiple life forms that inhabit our public urban spaces.